Estrogen and bacterial infection - Hong, Longyan; Liang, Hao; Man, Wenqing; Zhao, Yinghui; Guo, Pengbo (Frontiers in Immunology, 2025)
Gender differences exist in the susceptibility, incidence, progression, and prognosis of bacterial infections in males and females, influenced by various factors including lifestyle and habits. Multiple reports have indicated that estrogen plays a crucial immunomodulatory role in many pathogenic microbial infections, highlighting a complex relationship between estrogen, its receptors, and bacterial infections. Estrogen and its receptors regulate host immune responses, affecting the host’s ability to clear bacteria and thus influencing the likelihood and difficulty of infection eradication. Variations in estrogen levels may lead to differences in the occurrence and progression of bacterial infections, with estrogen playing varied roles in diseases caused by the same bacterial pathogens. The interaction between estrogen and bacterial infections represents a complex and crucial aspect of human physiology and clinical medicine. Understanding this interaction is essential for advancing infection prevention and treatment strategies. This article reviews the correlation and mechanisms between estrogen and bacterial infections, emphasizing the importance of further research in this field.